Influence of Human Resource Practices on Employee Job Satisfaction in Nepalese Commercial Banks - Chand , Umesh (Journal of Research in Education, 2025)
Employee job satisfaction continues to be a serious concern of commercial banking because of its strong impression on motivation, performance and the rate at which employees can leave. Studies in this area are emerging globally, but empirical evidence in Nepal is inadequate and fragmented on the common impact of different HR practices on job satisfaction. The Current study intends to bridge the gap as it examines the impact of six HR practices -performance appraisal, training and development, rewards system, recognition and non-monetary rewards, promotion and work career growth and work life balance on employees’ job satisfaction in commercial banks of Nepal. Cross sectional descriptive quantitative research design was used and a structured Likert scale questionnaire was administered to 312 participants. Descriptive statistics and Pearson’s correlation were used for the analysis. The findings in the study show significant and positive relationship of all HR practices with job satisfaction, it includes promotion and career development (.493), r=. 58, p